The effect of different dielectrics on material removal rate, surface roughness and white layer thickness in EDM process - H. Aghdeab, Shukry; L. Aldulaimy, Haneen; L. Aldulaimy, Haneen (International Journal of Engineering and Technology, 2018)
The electrical discharge machining (EDM) is a highly non-traditional manufacture method in which material exclusion happens because of repeated electrical discharges at small periods in the presence of a dielectric medium. It is adopted in numerous processes involving the industry of dies and molds, surface alloying, surface texturing of steel rolls, manufacture of aero engine parts and manufacture of the metallic prosthesis. In EDM, the key output factors are the material removal rate (MRR), the surface roughness (SR) and white layer thickness (WLT). The operational fluid has an imperative function in machining and effecting the MRR, SR, WLT and the properties of the machined surface. This study aims to investigate the influence of using different dielectric such as vegetable oil, transformer oil and gas oil to obtain the maximum MRR with lower surface roughness and minimum whit layer thickness in EDM for stainless steel 316L specimens with a copper electrode. The result shows that the vegetable oil can be used as a dielectric in EDM, it gives extreme MRR while the relative SR is lower and higher WLT when compared to transformer oil and gas oil. Analysis of variance results indicated that the current and pulse-on-time are the most important factors that effect on MRR, SR and WLT. The MRR in vegetable oil and transformer oil produced 66% and 61% higher MRR, respectively, than gas oil. Additionally, vegetable oil and transformer oil resulted in 38% and 13% lower SR than gas oil, while vegetable oil and transformer oil resulted 28% and 14% higher in WLT than gas oil.